Effects of Social Skills Training for Drug Users under Treatment - Jéssica Limberger; Ilana Andretta (2022)
Abstract The Social Skills Training (SST) presents satisfactory results in different clinical and non-clinical populations. The objective of this study is to evaluate the effects of SST on the perception of quality of life of drug users under treatment in post-intervention and follow-up conditions. It is a quasi-experimental study. The instruments used in the study were: CHASO, EMES-M, Extensive Interaction Semi-structured Test and WHOQOL. The study sample was composed of forty male drug users who participated in SST in a Therapeutic Community. The results indicate a statistically significant increase in the ability of defending rights, dealing with and keeping calm upon criticism, with medium effect size on the ability to refuse requests, refuse drugs and quality of life (psychological domain). SST was found to contribute to the development of specific social skills and as a complementary strategy in the Therapeutic Community.